If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 + 8u = -50 Solving -2 + 8u = -50 Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 8u = -50 + 2 Combine like terms: -2 + 2 = 0 0 + 8u = -50 + 2 8u = -50 + 2 Combine like terms: -50 + 2 = -48 8u = -48 Divide each side by '8'. u = -6 Simplifying u = -6
| 296+x-24+29=360 | | -2(5s+2)+5(s-3)= | | 5x+3=8x+2 | | N/5-(-11)=9 | | 13.5(n)=189 | | 8-x/5=22 | | -11-12g=-71 | | 9(4-s)=10+45 | | 2(2)+3x=24 | | 40(n)=324 | | 34-8x=16+10x | | Y^2-2y+5-8y+10=0 | | 5(h-2)-6(h+1)= | | x+17+2x+1=90 | | 3(n)=210 | | -165=13a | | 17(b-4)= | | 200=x^3+4x^2+4x | | X-2=11/24 | | 22x-3=20+10x | | F/10-11=9 | | 18=9x-7 | | L=1+-3w | | 4(4x-4)=-144 | | 5(n)=126 | | 7+4(x-4)-10=-45 | | 3+3x=4x+20 | | 13=×/3-22 | | 50/X-60=51.666 | | 2x-15+3(x-1)=13 | | 2x+3(8)=24 | | 7x-7*2=49 |